Makna Pernikahan Bagi Wanita Lajang Usia Dewasa - Andu, Christine Purnamasari (representamen, 2019)
The research aims to know (1) the meaning of marriage for adult single women and (2) the biggest fear aboutmarriage. The research used qualitative descriptive methods. The research was conducted in Makassar citywhere types and data sources used primary and secondary data. Primary data or main data is taken frominterview and secondary data or supporting documents are collected from books, dissertation, theses,journals, articles, and internet. There were 10 (ten) informants as samples were interviewed and the results ofthese interviews were analyzed using several theories. The research result indicate that (1) 80% informantswhich were interviewed by researcher said that marriage does not have to be rushed and considered thatmarriage at their present age is not a very important thing to be soon celebrated, and the rest informantsconsidered that marriage is very important considering the growing age. Some of informants also assume thatmarriage is very important but selecting the person is not an easy thing to be done because of manyconsiderations. Some of them also said that marriage is important but only see that thing as a fulfillment forsocial needs (2) 70% informants answered that their biggest fear in marriage are divorce, domestic violence,and there are also another response such us wrong choice, financial instability, rude, and unfaithfulness.Keywords: Marriage, Single Woman, Adulthood